Academic Digital Libraries and Semantic Web: Elements for the Innovation of Library and Information Services - Ávila Barrientos, Eder (2016)
The academic digital library is a system that has been developed through the use of information and communication technologies. Its origin goes back to research projects at various universities and academic institutions around the world. As part of their evolutionary development, now is immersed in the digitalcontext of the semantic web, a web extended and equipped with greater meaning, based on universal languages, will allow users to find answers to your questions more efficiently and effectively through the establishment of meaningful relationships of information. The objective of this work lies in the presence of digital academic libraries in the semantic web, to identify the elements that foster innovation in library and information services. Supported the documentary analysis and hermeneutic and discourse analysis, they are located and analyze various information resources of literature specializing in library and informationstudies addressing the objects of study presented in this article.